Stem cell mobilization in patients with dialysis‐dependent multiple myeloma: Report of the Polish Myeloma Study Group. Issue 3 (18th September 2017) - Waszczuk‐Gajda, Anna; Drozd‐Sokołowska, Joanna; Boguradzki, Piotr; Dybko, Jarosław; Wróbel, Tomasz; Basak, Grzegorz Władysław; Mądry, Krzysztof; Snarski, Emilian; Charliński, Grzegorz; Frączak, Ewa; Matuszkiewicz‐Rowińska, Joanna; Klinger, Marian; et al.
Abstract: Introduction: High‐dose chemotherapy with autologous hematopoietic stem cell transplantation (auto‐HSCT) improves the outcome of patients with multiple myeloma (MM). It seems that auto‐HSCT is also a feasible therapeutic option in MM dialysis‐dependent (MMDD) patients. However, to perform transplantation, a sufficient number of stem cells must be collected. Materials and Methods: Given that data on mobilization of auto‐HSC efficacy and safety in dialysis‐dependent patients are limited, we report data from all Polish Centers belonging to the Polish Myeloma Study Group. Twenty‐eight dialysis‐dependent MM‐patients were enrolled into this retrospective analysis. The study population comprised patients diagnosed between 2004 and 2015 in whom an attempt to collect auto‐HSC was made (68%: women, median age: 56). Patients received granulocyte‐colony stimulating factor (G‐CSF) alone or in combination with chemotherapy and autologous peripheral blood stem cells (auto‐PBSCs) were collected by leukapheresis. Results and Conclusions: The success rate in terms of obtaining sufficient number of CD34(+) cells/kg for an auto‐HSCT (≥2 × 10 6 cells/kg body weight) during the first mobilization attempt was 92% (26/28 patients), and for 2 auto‐HSCTs (≥4 × 10 6 cells/kg) – was 75% (21/28 patients). After the second mobilization attempt (undertaken in 8 patients), a sufficient number of CD34(+)/kg cells for an auto‐HSCT was obtained for all patients and the number of CD34(+)/kg collected cells was sufficient for 2 auto‐HSCT in 6 additional patients. Hematologic toxicity and infections were the most frequent complications. Higher doses of cytarabine (>1.6 g/m 2 ) and cyclophosphamide (> 2 g/m 2 ) should be avoided in MMDD patients due to toxicity. Further studies are needed to establish mobilization regimens, confirm their safety, and dosing in MMDD patients.